KEPASTIAN HUKUM PERALIHAN HAK ATAS TANAH MELALUI JUAL BELI BERDASARKAN SKT - Karlina, Kiki; Wiko, Garuda; Alhadiansyah, Alhadiansyah (Faculty Of Law, Universitas Tanjungpura, 2023)
ABSTRACTThe SKT which has been owned by the people of the village of Kuala Tolak and has been signed and approved by the village head can be used as the basis for making land certificates at the Ketapang BPN office, based on the Jurisprudence of the Supreme Court on December 13, 1958 No. 4/K/RUP/1958SKT, namely the village head is legal under customary law. The problem raised is how the legal certainty of the people of the Kuala Tolak village who sells and buys land rights based on buying and selling through SKT. The method used by researchers in the preparation of this thesis is descriptive analysis to describe the existing situation by using scientific research methods and solving problems based on the data and facts collected as they were when this research was conducted. From the results of the study, it can be found that in 2022 in the village of Kuala Tolak, North Matan Hilir Sub-District, there are still many people who buy and sell property rights to land based on SKT, buying and selling land carried out by the people of Kuala Tolak Village based on SKT can be registered at the BPN office in Ketapang City. Provided that the applicant brings SKT in his name as well as SKT-SKT and a Letter of Release of land rights from the previous land rights holder, as well as a Letter of Introduction from the Village. The people